A research of drug addiction and influential factors in high school students - Hacıhasanoğlu, Rabia; Türkleş, Serpil; Yıldırım, Arzu; Karakurt, Papatya (Journal of Dependence, 2009)
Objective: This study was conducted to evaluate the drug addiction and influential factors of the 9nt, 10th and 11th year students at high school students who are educated in 12 high school of Erzincan county.Method: TThe contex of this descriptive and cross-sectional study consists of a total of 4962 students who attended the above mentioned schools and the sampling comprised911 students (18% of the contex) randomly chosen among them. The data were collected in April 2007 through a descriptive form designed by the researchers and were evaluated using percentage calculations and chi-square test.Results: It was determined that 11.2% of the students smoked, 3.4% used alcohol, 0.1% used cocain, 0.3% used eroine, 0.7% used ecstasy, 1.9% used volatile substances which were glue, bally lacques, paint thinners.The using of cigarette of the students was affected by the factors such as age, gender, circumstances of study, school success, using alcohol and cigarette of the students, attitude of parents, getting along between parents, to believe of mother sincerity, abusing from father, whether the student shared his/her problems with his/her parents, loneliness. The using of alcohol was affected by to believe of mother sincerity, abusing from parents, cigarette and alcohol using of family members.Conclusion: In this study, the using rates of smoke, alcohol and drug of high school students were low compared to similar studies but, to use of drug in early ages can lead to permanent and chronic health problems. Finally, the prevalence of use smoke, alcohol and drug is not very high, but it is not a desired level either. So, it can be recommended that relevant and preventive measurements must be provided to make them stay away from the hazardous substances.
Keywords: High school students; cigarettes; alcohol; drug addiction